Don’t They Know They are in Over Their Heads? - Diane Erickson (Adult Education Research Conference, 2008)
Using the Subject-Object Interview data was gathered to assess the meaning making framework underlying meaning construction by peer instructors in learning in retirement programs. Construction of the peer instructing experience was consistent with the potential depth and breadth of assessed meaning making capacity, but not the expectations of the role.
Keywords: adult development; constructivism; peer instruction